Estudo de associações de polimorfismos genéticos no gene COL2A1 e condições bucais - Rechia, Bruna Cristina do Nascimento (2019)
Introduction: Temporomandibular Disorder (TMD) and Dental Fluorosis (DF) are multifactorial conditions that associate environmental with psychological and genetic conditions. Objective: To investigate the association between genetic polymorphisms of the COL2A1 gene with TMD and DF in a population of adolescents living in the city of Curitiba. Materials and methods: In this case-control study, 253 adolescents between 10 and 14 years old, diagnosed with TMD by RDC / TMD criteria, and diagnosed with dental fluorosis by the modified Dean index. The group affected by TMD was subdivided according to the RDC / TMD criteria: myofascial pain (with or without opening limitation), disk displacement (with or without reduction) and arthralgia. For dental fluorosis, subjects were divided into two groups: presence of fluorosis and absence of fluorosis. Genomic DNA was extracted from buccal cells by mucosal scraping and genetic polymorphisms in COL2A1 were genotyped by real-time polymerase chain reaction using the TaqMan assay. Results: 148 individuals were diagnosed with TMD. There were no significant differences between the affected and non-affected individuals (p> 0.05) for TMD, arthralgia, and myofascial pain, although polymorphism rs2276454 was considered borderline in the genotypic distribution (p = 0.07) and was associated with disc displacement (p = 0.03) in the allelic distribution. In the recessive model there was a significant association between affected and unaffected individuals (p = 0.02) due to disc displacement. 25 individuals were diagnosed with DF and there were no significant differences between affected and non-affected individuals (p> 0.05). Conclusion: genetic polymorphisms in COL2A1 were associated with mandibular disc displacement in individuals with TMD. There were no significant associations between the same genetic polymorphisms with DF.